UNDERSTANDING THE RELATIONSHIP BETWEEN UNETHICAL BEHAVIOUR AND CUSTOMER BRAND IMAGE: A CASE STUDY ON H&M - Hanan Nakdali; Manzar Ahmed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study is conducted to determine the relationship between unethical behavior and customer brand image. The main focus is to understand this relationship regarding the clothing industry. The clothing industry is very wide, and nowadays fast and cheap production has become a trend in the clothes market. Previous study about the effect of unethical behavior on people and purchase choices was made, but no study was made focusing on the relationship of unethical behavior and brand image, nor did it focus on the clothing industry. The methodology used in this study is two focus groups, one conducted in Saudi Arabia and one conducted in Spain. The aim of choosing different countries is to see if cultural and social differences have an effect on this topic. The results of this study prove that there is no direct impact of unethical behavior of brands on customer brand image. The results in both countries prove to be similar; therefore social differences do not really have an influence in this matter. This study helps to understand consumer behavior and what priorities do consumers have when purchasing a specific brand.